Total Quality Management: Konsep Peningkatan Mutu Pendidikan - Hasnadi Hasnadi (SAP (Susunan Artikel Pendidikan), 2021)
The Indonesian government has made efforts to implement numbers of excellent programs to improve the quality of education. However, the variety of challenges faced by schools effect the lack of optimal competition in the quality of education. The purpose of this article is to analyze and describe the concept of Total Quality Management (TQM) as an effort to improve the quality of education. This article uses a qualitative method with a literature review approach. The TQM concept is one of the concepts that can be applied to improve the quality of education. In applying the TQM concept to education, it is necessary to pay attention to several aspects, namely: (1) focus on graduate users, (2) obsession with quality, (3) scientific approach, (4) teamwork, (5) having a long-term commitment and sustainable, (6) continuous improvement efforts, (7) conducting education and training, (8) common perceptions and goals, (9) having a free and controlled organizational culture, and (10) engaging and empowering human resources. All aspects of TQM must be oriented to the education management system, the behavior of school members, focus on optimal service in order to meet the needs, and desires of the stakeholders.